Preparation and application of a corn straw-based biochar / manganese dioxide composite material film

CN118268033BActive Publication Date: 2026-10-27HEXI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410433879.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2026-10-27
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

然而由于单独制备的MnO2容易团聚,与臭氧和污染物的接触面积较小,严重影响了MnO2的催化效果

Benefits of technology

[0023]综上所述,本发明利用农业固体废弃物玉米秸秆为碳源、氰胺废渣为造孔剂,制备多孔碳。并将纳米二氧化锰负载在多孔碳材料上,对其催化臭氧降解百里酚蓝的性能进行探究。氰胺废渣进行氮掺杂的多孔碳表面含有大量的羟基和羧基官能团兼具比表面积大,有利于金属氧化物的负载,且氰胺废渣作为造孔剂在制备生物炭过程中使生物炭具有更多的孔结构和更大的比表面积,增大了催化剂和臭氧的接触面积。复合材料膜催化臭氧降解百里酚蓝的降解效果优异,经过反复试验发现当氰胺废渣与玉米秸秆粉的质量比例为1:10,MnO2与生物炭比例为1:10的时候复合材料膜对催化臭氧降解百里酚蓝的效果最好,达到了96.832%。复合材料在经过四次循环后降解率没有明显降低,仍可达94%以上,说明催化剂有较好的稳定性;通过对催化机理的研究在复合材料膜催化臭氧降解百里酚蓝的体系中起起主要作用的是·O2-,其次是·OH。本发明原料廉价易得,变废为宝使资源得到二次利用的同时有效提高了催化臭氧降解酚类废水的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a corn straw-based biochar / manganese dioxide composite material membrane and a preparation and application thereof. The application uses agricultural solid waste corn straw as a carbon source and cyanamide waste residue as a pore forming agent to prepare porous carbon. Nano-manganese dioxide is loaded on the porous carbon material to obtain a porous biochar loaded manganese dioxide composite membrane. The degradation effect of the composite material membrane on phenolic wastewater is investigated by using thymol blue as a simulation, and the degradation rate of thymol blue can reach more than 96%. After the composite material membrane is used repeatedly for four times, the degradation rate of thymol blue in the catalytic ozone degradation system of the composite material membrane is not obviously reduced, and can still reach more than 94%, which indicates that the catalyst has good stability. Through the research on the catalytic mechanism, it is found that ·O2- plays a main role in the system of the composite material membrane catalyzing ozone to degrade thymol blue. ‑ The raw materials of the application are cheap and easy to obtain, waste is turned into treasure, resources are secondarily utilized, and the effect of catalytic ozone degradation of phenolic wastewater is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment and catalytic material preparation technology, and relates to a method for preparing a biochar / manganese dioxide composite membrane based on corn stalks, and also relates to the application of the biochar / manganese dioxide composite membrane in the catalytic ozone degradation of phenolic wastewater. Background Technology

[0002] Phenolic wastewater is one of the most harmful and widespread industrial wastewaters in the world today. Its treatment methods mainly include physical, chemical, and biochemical methods, with biochemical methods being the most cost-effective. However, phenols are recalcitrant biodegradable substances, and high phenol concentrations in wastewater can inhibit the growth of microorganisms used in wastewater treatment. Therefore, many researchers have developed advanced oxidation technologies to treat this type of wastewater, such as ozone oxidation, a highly efficient method for phenol removal because ozone has a high redox potential (2.07V, only lower than fluorine and hydroxyl radicals). However, ozone molecules exhibit strong selectivity in oxidizing organic matter, resulting in a low reaction rate and low solubility in water, thus failing to completely remove organic matter. Therefore, in recent years, scholars both domestically and internationally have focused their attention on heterogeneous catalytic ozone oxidation technology.

[0003] Cyanamide is produced through processes including calcium cyanamide hydrolysis, decalcification, polymerization, crystallization, filtration, and drying. The decalcification process generates a large amount of waste residue, which occupies significant land. In my country, cyanamide production is mainly concentrated in northern regions rich in coal and electricity resources. However, the arid climate, low rainfall, and strong winds of northern China easily lead to environmental pollution. Furthermore, cyanamide producers must pay for waste residue treatment, making it a bottleneck for their long-term development. Literature indicates that cyanamide waste residue contains approximately 80% CaCO3 and 20% cyanamide. Since CaCO3 is the main component of cyanamide waste residue, and it is relatively cheaper and more readily available than CaCO3, we hope to find new treatment methods for cyanamide waste residue through research, turning waste into treasure and enabling resource reuse.

[0004] Biochar has a wide range of readily available and inexpensive raw materials, and with the development of the times and the advancement of science and technology, people have discovered that carbonaceous materials hold unlimited potential. Among various carbonaceous materials, porous carbon materials possess highly developed pore structures, large specific surface areas, and excellent electrical conductivity, and are therefore widely used in energy storage and conversion, catalysis, and other fields. The pore size of porous carbon materials has a significant impact on their practical application performance. The doping of heteroatoms also has a great influence on the performance of porous carbon materials. Heteroatom doping not only improves the catalytic activity and electrocatalytic performance of porous carbon materials, but also enhances their antioxidant properties.

[0005] Manganese dioxide (MnO2) is inexpensive, abundant, exhibits good catalytic performance, is environmentally friendly, easy to prepare, and possesses excellent oxygen reduction and hydrogen peroxide decomposition activity. MnO2 exists in various crystal forms (α, β, γ, δ, etc.), with δ-MnO2 belonging to a two-dimensional layered structure. It possesses advantages such as low zero-point charge, numerous acidic sites, and good adsorption and oxidation properties, making it an effective adsorbent material. However, because MnO2 prepared alone tends to aggregate, its contact area with ozone and pollutants is small, severely affecting its catalytic effect. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a biochar / manganese dioxide composite membrane based on corn stalks, and to provide the application of this biochar / manganese dioxide composite membrane in the catalytic ozone degradation of phenolic wastewater.

[0007] I. Preparation of Biochar / MnO2 Composite Membranes (1) Preparation of porous biochar based on corn stalks The mixture of cyanamide waste residue and corn stalk powder was ultrasonically mixed to ensure thorough mixing. The mixture was then placed in a ceramic boat, which was placed in a tube furnace and nitrogen gas was introduced as a protective gas. The temperature was raised to 450-550℃ (5℃ / min) and held for 1.5-2.5 hours. After cooling to room temperature, biochar was obtained. The biochar was added to hydrochloric acid, magnetically stirred, filtered, and washed with deionized water and anhydrous ethanol to remove calcium chloride. The biochar was then dried and ground to obtain porous biochar. The mass ratio of cyanamide waste residue to corn stalk powder was 1:10-1:20.

[0008] (2) Preparation of MnO2 Potassium permanganate was placed in a mortar and ground. The ground powdered potassium permanganate was then transferred to a ceramic crucible and calcined in a muffle furnace at 300-400℃ (5℃ / min) for 4-6 hours. After natural cooling, it was taken out and washed with distilled water until the filtrate was colorless. The water was then dried to obtain δ-MnO2, which was then ground for later use.

[0009] (3) Preparation of biochar / MnO2 composite material based on corn stalks Porous biochar and MnO2 were mixed and added to 100 mL of deionized water. The mixture was then magnetically stirred and ultrasonically dispersed to ensure thorough mixing. Finally, the dispersion was placed in a water bath at 75-85°C and stirred for 5-6 hours. The mixture was then removed, filtered, washed with deionized water and anhydrous ethanol, dried, and ground to obtain the biochar / MnO2 composite material. The mass ratio of MnO2 to porous biochar was 1:5 to 1:20.

[0010] (4) Preparation of biochar / MnO2 composite membrane based on corn stalks The biochar / MnO2 composite material was dispersed in acetone and ultrasonically dispersed to ensure uniform mixing. Polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) was dissolved in N,N-dimethylformamide to prepare a transparent solution. The two liquids were mixed and ultrasonically continued. The dispersion was then heated and stirred in a 35-45°C water bath to evaporate the acetone. The remaining dispersion was poured off and the film was laid on a filter. After the edges of the film were slightly dry, the filter with the film was immersed in deionized water for membrane removal, yielding a corn stalk-based biochar / MnO2 composite membrane. The mass ratio of the biochar / MnO2 composite material to the PVDF-HFP copolymer was 1:2 to 1:3.

[0011] II. Structure of Biochar / MnO2 Composite Membrane 1. Digital photograph of composite membrane Digital photographs of biochar / MnO2 composite membranes, such as Figure 1 The membrane surface is smooth and has a certain degree of elasticity, which effectively solves the problem of catalyst powder being difficult to recycle.

[0012] 2. Scanning electron microscopy characterization of biochar, biochar / MnO2 composite material, and biochar / MnO2 composite material membranes. Figure 2 Scanning electron microscope (SEM) images of biochar, biochar / MnO2 composite, and biochar / MnO2 composite membranes. From... Figure 2 a and Figure 2 In these two figures, it can be clearly observed that the biochar prepared from corn stalk powder has a lamellar structure. The surface of the lamellars is porous and uneven, providing space for catalyst adhesion. From Figure 2 c and Figure 2 In these two figures, we can see that the loading of manganese dioxide disrupts the layered structure of biochar. The originally blocky biochar surface is further exfoliated into carbon nanosheets, making the biochar surface rough and creating many micropores, which increases the specific surface area. Figure 2 Some porous structures can be observed, indicating that the biochar we produced retains the porous structure of corn stalks, and many spherical particles such as... can also be observed in the micropores. Figure 2 As shown in f, these spherical particles are MnO2.

[0013] 3. X-ray diffraction patterns of biochar, manganese dioxide, and biochar / MnO2 composite materials. Figure 3The X-ray diffraction patterns of biochar (C3), manganese dioxide (MnO2), and biochar / MnO2 composites (C3&MnO2) are shown. Analysis reveals that the MnO2 produced is δ-MnO2. δ-MnO2 has a monoclinic structure and is a layered structure on the (001) crystal plane, which is a two-dimensional plane. The figures clearly show the characteristic diffraction peaks of δ-MnO2 after loading onto the biochar, suggesting that δ-MnO2 has been loaded onto the biochar.

[0014] 4. Infrared spectral characterization of biochar, manganese dioxide, and biochar / MnO2 composite materials Figure 4 The images show the FTIR spectra of biochar (C3), manganese dioxide (MnO2), and a biochar / MnO2 composite material (C3 & MnO2). In the manganese dioxide and composite materials, we can see that at 3344 cm⁻¹... -1 1658cm -1 1403cm -1 520cm -1 Characteristic peaks appeared in all four places. These characteristic peaks were generated by the stretching and bending vibrations of interlayer water, Mn atoms, OH bonds, and Mn-O bonds, respectively. These characteristic peaks did not appear in biochar, but they can be clearly seen in the composite material, which proves that manganese dioxide has been loaded onto biochar.

[0015] III. Biochar / MnO2 composite membrane catalyzes ozone degradation of thymol blue 1. Effect of the mass ratio of cyanamide waste residue to corn stalk powder on the catalytic ozone degradation of thymol blue. The catalytic degradation effect of thymol blue on phenolic wastewater was investigated. Three biochar membranes (composite membranes prepared at different mass ratios of cyanamide residue and corn stalk powder were C1&MnO2, C2&MnO2, and C3&MnO2 membranes, respectively) were added to 200 mL of 100 mg / L thymol blue solution. The ozone output was kept constant at 500 mg / h. Samples were taken every 10 min using a syringe, filtered through an MCE head (0.22 μm, aqueous system), and the filtrate was analyzed using a 7230G visible spectrophotometer at λ... max The absorbance was measured at 420 nm, and the degradation rate of thymol blue was analyzed to determine the optimal ratio of cyanamide residue and corn stalk powder in biochar.

[0016] Figure 5 The graph shows the effect of different mass ratios of cyanamide waste residue and corn stalk powder (1:100, C1), 1:20, 1:10 (C3), and pure MnO2 on the degradation rate of thymol blue under the same conditions. Figure 5 We can clearly see that among the different biochar types C1, C2, and C3, C3 exhibits the best degradation effect, with a degradation rate of 68.457%. Among the composite membranes, the C3 & MnO2 composite membrane demonstrates the best catalytic effect, with a degradation rate of 96.832%, which is 1.414 times the degradation rate of thymol blue catalyzed by biochar with ozone, and 1.083 times the degradation rate of thymol blue catalyzed by MnO2 with ozone.

[0017] 2. Effect of different MnO2 addition amounts in biochar / MnO2 composite membranes on the catalytic ozone degradation of thymol blue Four membranes were prepared using MnO2 and biochar (prepared from cyanamide waste residue and corn stalk powder at a mass ratio of 1:10) at mass ratios of 1:20, 1:10, 3:20, and 1:5. Each membrane was added to 200 mL of 100 mg / L thymol blue solution, and the ozone output was kept constant at 500 mg / h. Samples were drawn every 10 minutes using a syringe, filtered through a 0.22 μm aqueous filter, and the filtrate was measured using a 7230G visible spectrophotometer to determine the λ value. max The absorbance at 420 nm was analyzed, and the degradation rate of thymol blue was determined to identify the optimal ratio of MnO2 to biochar.

[0018] Figure 6 The graph shows the effect of different mass ratios of MnO2 (C3:MnO2=1:20, 1:10, 3:20, 1:5) on the degradation rate of thymol blue under the same conditions when the mass ratio of cyanamide waste residue to corn straw powder is 1:10. By comparing the line graphs, we can see that the composite material has the best catalytic effect when C3:MnO2=1:10, with a degradation rate of 96.832%.

[0019] 3. Stability Study of Ozone Degradation of Thymol Blue Catalyzed by Biochar / MnO2 Composite Membrane Take 200 mL of 100 mg / L thymol blue solution in a beaker, add an optimal ratio of biochar / MnO2 composite membrane (C3 & MnO2), keep the ozone output constant at 500 mg / h, take a sample every 10 min using a syringe, filter with an MCE head (0.22 μm, aqueous system), and analyze the filtrate using a 7230G visible spectrophotometer at λ. max The absorbance was measured at 420 nm. After degradation was complete, 200 mL of 100 mg / L thymol blue solution was added again for catalytic degradation. The cycle was repeated four times to evaluate the stability of the biochar / MnO2 composite (C3&MnO2) membrane.

[0020] Figure 7The figure shows the stability of the composite membrane in catalyzing the degradation of thymol blue by ozone. As can be clearly seen from the figure, the degradation rate of thymol blue by ozone catalyzing the composite membrane does not change much after four cycles, and the degradation rate remains above 94%, indicating that the catalyst has good stability.

[0021] 4. Mechanism of ozone degradation of thymol blue catalyzed by biochar / MnO2 composite membrane Take 200 mL of 100 mg / L thymol blue solution in a beaker, add 4 mL of tert-butanol, 4 mL of methanol, 20 mg of sodium oxalate, and 20 mg of p-benzoquinone, respectively, and add a biochar / MnO2 composite membrane. Maintain the ozone output at a constant 500 mg / h. Take a sample every 10 minutes using a syringe, filter with an MCE head (0.22 μm, aqueous system), and measure the ozone output at λ using a 7230G visible spectrophotometer. max The absorbance at 420 nm was measured, and the degradation rate of thymol blue was analyzed to explore the mechanism of ozone degradation of thymol blue by composite membrane.

[0022] Figure 8 This diagram shows the degradation of thymol blue by ozone catalyzed by the composite membrane when four different inhibitors—methanol, tert-butanol, sodium oxalate, and p-benzoquinone—are added to the catalytic system. Tert-butanol is an ·OH radical inhibitor, and p-benzoquinone is an ·O2 radical inhibitor. - Methanol and sodium oxalate are free radical inhibitors, acting as hole inhibitors. When tert-butanol was added to the catalytic system, the degradation rate of thymol blue decreased, indicating that ·OH free radicals affect the degradation rate of thymol blue during the catalytic ozone degradation process of the composite membrane. While the degradation rate of thymol blue decreased slightly when methanol and sodium oxalate were added, the decrease was not significant, suggesting that holes play a limited role in the catalytic system. The addition of p-benzoquinone resulted in a substantial decrease in the degradation rate of thymol blue, leading to the conclusion that ·O2... - Free radicals play a crucial role in catalytic systems. Therefore, based on the above experimental results, it can be inferred that in the composite membrane catalytic system for the ozone degradation of thymol blue, ·OH free radicals and ·O2 free radicals play a vital role. - Free radicals are important oxidative free radicals in catalytic systems, with ·O2 playing a major role. - Free radicals.

[0023] In summary, this invention utilizes agricultural solid waste, corn stalks, as a carbon source and cyanamide residue as a pore-forming agent to prepare porous carbon. Nano-manganese dioxide is then loaded onto the porous carbon material to investigate its catalytic performance in the ozone degradation of thymol blue. The nitrogen-doped porous carbon from cyanamide residue contains a large number of hydroxyl and carboxyl functional groups and has a large specific surface area, which is beneficial for the loading of metal oxides. Furthermore, the cyanamide residue, acting as a pore-forming agent, imparts more pore structures and a larger specific surface area to the biochar during preparation, increasing the contact area between the catalyst and ozone. The composite membrane exhibits excellent catalytic degradation effect of thymol blue. Repeated experiments revealed that when the mass ratio of cyanamide residue to corn stalk powder is 1:10 and the ratio of MnO2 to biochar is 1:10, the composite membrane achieves the best catalytic degradation effect of thymol blue, reaching 96.832%. The degradation rate of the composite material did not decrease significantly after four cycles, remaining above 94%, indicating good catalyst stability. Research on the catalytic mechanism revealed that ·O2 plays a major role in the composite membrane-catalyzed ozone degradation of thymol blue system. - Secondly, ·OH. The raw materials used in this invention are inexpensive and readily available, turning waste into treasure and enabling the secondary utilization of resources while effectively improving the catalytic ozone degradation effect on phenolic wastewater. Attached Figure Description

[0024] Figure 1 Digital photograph of a biochar / MnO2 composite membrane; Figure 2 a-SEM image of biochar at 500 nm; b-SEM image of biochar at 5 μm; c-SEM image of biochar / MnO2 composite material at 500 nm; d-SEM image of biochar / MnO2 composite material at 5 μm; e-SEM image of biochar / MnO2 composite film at 5 μm; f-SEM image of biochar / MnO2 composite film at 200 nm. Figure 3 X-ray diffraction patterns of C3, MnO2, and C3&MnO2; Figure 4 Infrared comparison images of C3, MnO2, and C3 & MnO2; Figure 5 The figure shows the effect of the amount of cyanamide waste added to the composite membrane on the degradation rate of thymol blue by catalytic ozone degradation of the composite membrane. Figure 6 The figure shows the effect of MnO2 addition in the composite membrane on the degradation rate of thymol blue by catalytic ozone degradation. Figure 7 The graph shows the effect of cycle number on the catalytic degradation of thymol blue by the composite membrane using ozone. Figure 8A diagram illustrating the mechanism of ozone degradation of thymol blue catalyzed by a biochar / MnO2 composite membrane. Figure 9 The graph shows the linear relationship between the absorbance of thymol blue and the standard concentration. Detailed Implementation

[0025] The present invention will be further described below through specific embodiments.

[0026] The reagents and instruments used in this invention are as follows: Example 1 (1) Preparation of biochar based on corn stalks A mixture of cyanamide waste residue and corn stalk powder at a mass ratio of 1:10 was ultrasonically mixed for 1 hour to ensure thorough mixing. The mixture was placed in a ceramic boat, which was then placed in a tube furnace with nitrogen as a protective gas. The temperature was raised to 500℃ (5℃ / min) and held for 2 hours. The mixture was then cooled to room temperature to obtain three biochar samples with different mass ratios of cyanamide waste residue and corn stalk powder. 4g of each of the three different biochar samples was added to 400mL of 0.1mol / L hydrochloric acid and magnetically stirred for 30 minutes. The samples were then filtered and washed with deionized water and anhydrous ethanol to remove calcium chloride. The biochar samples were dried and ground to obtain porous biochar C3.

[0027] (2) Preparation of MnO2 A certain amount of potassium permanganate was placed in a mortar and ground for 30 minutes. 2g of the ground powdered potassium permanganate was weighed and transferred to a ceramic crucible. The crucible was calcined in a muffle furnace at 350℃ (5℃ / min) for 5 hours. After natural cooling, the crucible was removed and washed with distilled water until the filtrate was colorless. The crucible was then placed in an oven and dried at 60℃ to remove moisture, thus obtaining δ-MnO2. Finally, the crucible was ground for later use.

[0028] (3) Preparation of biochar / MnO2 composite material based on corn stalks MnO2 and porous biochar (C3) were mixed at a mass ratio of 1:10 and placed in a beaker with 100 mL of deionized water. The mixture was magnetically stirred for 30 min and then ultrasonically dispersed for 30 min to ensure thorough mixing. Finally, the dispersion was placed in an 80 °C water bath and stirred for 6 h. The mixture was then removed, filtered, and washed with deionized water and anhydrous ethanol. It was then dried in an oven at 60 °C for 1 h, ground, and prepared as a biochar / MnO2 composite material (C3 & MnO2).

[0029] (4) Preparation of biochar / MnO2 composite membrane based on corn stalks Weigh 50 mg of biochar / MnO2 composite material and disperse it in 5 mL of acetone. Sonicate the mixture for 30 min to ensure uniform mixing. Dissolve 120 mg of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) in 2 mL of N,N-dimethylformamide (DMF) to prepare a transparent solution. Mix the two liquids and continue sonicating for 30 min. Then, heat and stir the dispersion in a 40°C water bath to evaporate the acetone. Pour off the remaining dispersion and lay it on a filter. After the edges of the membrane are slightly dry, immerse the filter with the membrane in deionized water to remove the membrane, obtaining the C3 & MnO2 composite membrane.

[0030] (5) Degradation performance: The C3 & MnO2 composite membrane was added to 200 mL of 100 mg / L thymol blue solution. The ozone output was kept constant at 500 mg / h. Samples were drawn every 10 min using a syringe, filtered through an MCE head (0.22 μm, aqueous system), and the filtrate was measured using a 7230G visible spectrophotometer. max =Absorbance at 420nm. The degradation rate of thymol blue was calculated based on the absorbance vs. concentration standard curve of thymol blue. The degradation rate of thymol blue by ozone catalysis using the C3 & MnO2 composite membrane was 96.832%.

[0031] Construction of the absorbance-concentration standard curve for thymol blue: Prepare thymol blue solutions (0 mg / L, 20 mg / L, 40 mg / L, 60 mg / L, 80 mg / L, 100 mg / L) and measure their absorbance. Plot the linear relationship between the absorbance A and the standard concentration C of thymol blue, such as... Figure 9 As shown.

[0032] Example 2 In Example 1, the mass ratio of cyanamide waste residue to corn stalk powder in step (1) was replaced with 1:20, while the remaining steps were the same as in Example 1, to prepare a C2&MnO2 composite membrane. The C2&MnO2 composite membrane catalyzed the degradation of thymol blue by ozone at a rate of 94.771%.

[0033] Example 3 The mass ratio of MnO2 to porous biochar (C3) in step (3) of Example 1 was replaced with 1:5, and the remaining steps were the same as in Example 1. The biochar / MnO2 composite membrane was prepared with a 95.755% degradation rate of thymol blue by ozone catalysis.

[0034] Example 4 The mass ratio of MnO2 to porous biochar (C3) in step (3) of Example 1 was replaced with 1:20, and the remaining steps were the same as in Example 1. The biochar / MnO2 composite membrane was prepared with a thymol blue degradation rate of 89.885% catalytic ozone degradation.

Claims

1. A method for preparing a biochar / manganese dioxide composite membrane based on corn stalks, comprising the following steps: (1) Preparation of porous biochar based on corn stalks The mixture of cyanamide waste residue and corn stalk powder was ultrasonically mixed to ensure thorough mixing. The mixture was then placed in a ceramic boat, which was placed in a tube furnace with nitrogen gas introduced as a protective gas. The temperature was raised to 450-550℃ at a heating rate of 5℃ / min and held for 1.5-2.5 hours. After cooling to room temperature, biochar was obtained. The biochar was added to hydrochloric acid, magnetically stirred, filtered, and washed with deionized water and anhydrous ethanol to remove calcium chloride. The biochar was then dried and ground to obtain porous biochar. The mass ratio of cyanamide waste residue to corn stalk powder was 1:10-1:

20. (2) Preparation of δ-MnO2 Potassium permanganate was placed in a mortar and ground. The ground powdered potassium permanganate was transferred to a ceramic crucible and calcined in a muffle furnace at a heating rate of 5℃ / min to 300~400℃ for 4~6 hours. After natural cooling, it was taken out and washed with distilled water until the filtrate was colorless. The water was dried to obtain δ-MnO2. Finally, it was taken out and ground for use. (3) Preparation of biochar / δ-MnO2 composite material based on corn stalks Porous biochar and δ-MnO2 were mixed and added to 100 mL of deionized water. The mixture was then magnetically stirred and ultrasonically dispersed to ensure thorough mixing. Finally, the dispersion was placed in a water bath at 75-85℃ and stirred for 5-6 hours. The mixture was then removed, filtered, washed with deionized water and anhydrous ethanol, dried, and ground to obtain the biochar / δ-MnO2 composite material. The mass ratio of δ-MnO2 to porous biochar was 1:5 to 1:

20. (4) Preparation of biochar / δ-MnO2 composite membrane based on corn stalks The biochar / δ-MnO2 composite material was dispersed in acetone and ultrasonically dispersed to ensure uniform mixing. Polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) was dissolved in N,N-dimethylformamide to prepare a transparent solution. The two liquids were mixed and ultrasonically continued. The dispersion was then heated and stirred in a water bath at 35-45°C to evaporate the acetone. The remaining dispersion was poured out and the membrane was laid on a filter sheet. After the edges of the membrane were slightly dry, the filter sheet with the membrane was immersed in deionized water to remove the membrane, thus obtaining a biochar / δ-MnO2 composite membrane based on corn stalks. The mass ratio of the biochar / δ-MnO2 composite material to the polyvinylidene fluoride-hexafluoropropylene copolymer was 1:2 to 1:

3.

2. The application of the corn stalk-based biochar / manganese dioxide composite membrane prepared by the method according to claim 1 in the catalytic ozone degradation of phenolic wastewater.

Citation Information

Patent Citations

  • Method for preparing coal-based porous activated carbon material by using cyanamide waste residues as template

    CN109319781A